2019
DOI: 10.1007/s13524-019-00789-z
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Racial Inequality in Infectious Disease Mortality in U.S. Cities, 1900–1948

Abstract: In the first half of the twentieth century, the rate of death from infectious disease in the United States fell precipitously. Although this decline is well-known and well-documented, there is surprisingly little evidence about whether it took place uniformly across the regions of the United States. We use data on infectious disease deaths from all reporting U.S. cities to describe regional patterns in the decline of urban infectious mortality from 1900 to 1948. We report three main results. First, urban infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…These studies focused on regional differences, or changes in health levels, and found significant associations between regional differences in health levels, particularly in regional mortality. Many studies have shown that socio-economic factors, rather than natural environment, play an important role in contributing to regional differences in mortality (6,8,(12)(13)(14)(15)(16). Their findings empirically proved the influence of medical resource on individual health level.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…These studies focused on regional differences, or changes in health levels, and found significant associations between regional differences in health levels, particularly in regional mortality. Many studies have shown that socio-economic factors, rather than natural environment, play an important role in contributing to regional differences in mortality (6,8,(12)(13)(14)(15)(16). Their findings empirically proved the influence of medical resource on individual health level.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Most of the research on mortality has focused on specific diseases, natural climates, and crises (2)(3)(4). Some studies of mortality focused on the categories of death on the basis of the analysis of the existing materials of the cause of death (5)(6)(7)(8). However, studies on the impact of socio-economic factors and regional characteristics on mortality have been emerging (9)(10)(11).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work suggested that higher UVB doses were associated with higher 25(OH)D concentrations, leading to reductions in the cytokine storm and the killing of bacteria and viruses that participate in pneumonia. African Americans had much higher mortality rates than white Americans for the period 1900-1948 [122]. The reasons CFRs were higher for "coloreds" than whites may include that they have higher rates of chronic diseases, are more likely to live in regions impacted by air pollution, and that with darker skin pigmentation, blacks have lower 25(OH)D concentrations.…”
Section: Pneumoniamentioning
confidence: 99%
“…Previous work suggested that higher UVB doses were associated with higher 25(OH)D concentrations, leading to reductions in the cytokine storm and killing of bacteria and viruses that participate in pneumonia. African Americans had much higher mortality rates than white Americans for the period 1900-1948 [122]. The reasons CFRs were higher for blacks than whites may include that they have higher rates of chronic diseases, are more likely to live in regions impacted by air pollution, and that with darker skin pigmentation, blacks have lower 25(OH)D concentrations.…”
Section: Rsvmentioning
confidence: 99%